Evaluating and measuring the value, use and impact of digital collections - Hughes, Lorna M. (London Facet Publishing, 2012)
"A huge investment has been made in digitizing scholarly and cultural heritage materials through initiatives based in museums, libraries and archives, as well as higher education institutions. The 'Digital Economy' is an important component of institutional planning, and much attention is given to the investment in digital projects and programmes. However, few initiatives have examined the actual use, value and impact of digital collections, and the role of digital collections in the changing information environment. As the creative, cultural and educational sector faces a period of restricted funding, it is timely to re-examine the use of the digital collections that have been created in the past twenty years, and to consider their value to the institutions that host them and to the communities of users they serve"--Publisher.
Introduction the value, use and impact of digital collections Lorna M. Hughes -- The digital library Andrew Prescott -- The digital museum Claire Hudson -- The digital archive Gillian Oliver -- A strategic approach to the understanding and evaluation of impact Ben Showers -- User needs in digitization Milena Dobreva, Andy O'Dwyer and Leo Konstantelos -- Measuring impact and use scholarly information-seeking behavior Claire Ross, Melissa Terras and Vera Motyckova -- The value and impact of digitized resources for learning, teaching, research and enjoyment Simon Tanner -- Using ICT methods and tools in arts and humanities research Lorna M. Hughes -- Creating a research data infrastructure policy and practicalities Ann Borda and Lyle Winton -- Improving sustainability of publicly funded digital resources David Robey.
Keywords: Digital libraries -- Collection development; Digital libraries -- Evaluation; Digital libraries -- Use studies; Library materials -- Digitization; Digital preservation